2004
DOI: 10.1111/j.1875-595x.2004.tb00282.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of home bleaching agents on the roughness and surface morphology of human enamel and dentine

Abstract: Under the careful guidance of a dentist, home bleaching can be thought a reliable treatment for both stained enamel and dentine, regardless of whether 10% or 15% CP is used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
3
6

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 13 publications
4
27
3
6
Order By: Relevance
“…9,27,28 However, other studies have reported different results with no statistically significant differences in tooth hard tissue characteristics, including enamel and dentin surface roughness, after bleaching with 10% and 15% carbamide peroxide. 17,18,[29][30][31] The discrepancies in the results of various studies might be attributed to differences in the formulation and concentration of bleaching agents; the duration of daily applications or treatment protocols; differences in study designs, including the environments in which the specimens are stored (eg, artificial or human saliva); the use of remineralizing agents; continuous use of fluoridated toothpastes; and the technique of toothbrushing during the procedure and after bleaching. 2,14,30,32,33 In the present study, tooth structures underwent surface changes after bleaching, and toothbrushing immediately after bleaching had a substantial role in increasing enamel surface roughness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,27,28 However, other studies have reported different results with no statistically significant differences in tooth hard tissue characteristics, including enamel and dentin surface roughness, after bleaching with 10% and 15% carbamide peroxide. 17,18,[29][30][31] The discrepancies in the results of various studies might be attributed to differences in the formulation and concentration of bleaching agents; the duration of daily applications or treatment protocols; differences in study designs, including the environments in which the specimens are stored (eg, artificial or human saliva); the use of remineralizing agents; continuous use of fluoridated toothpastes; and the technique of toothbrushing during the procedure and after bleaching. 2,14,30,32,33 In the present study, tooth structures underwent surface changes after bleaching, and toothbrushing immediately after bleaching had a substantial role in increasing enamel surface roughness.…”
Section: Discussionmentioning
confidence: 99%
“…2,9,10,17,18 The oral cavity is inhabited by many diverse microbial species, and most of these microorganisms, especially those responsible for caries or periodontitis, can only survive in the oral cavity when they adhere to rough surfaces. Therefore, the roughness of intraoral hard tissues can promote formation, maturation, and retention of plaque, resulting in increased risk of dental caries, periodontitis, or tooth discoloration.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies [28][29][30] that investigated the surface morphology using SEM found no significant changes following bleaching. In contrast, using SEM, Covington and others 31 reported that changes occurred in the surface morphology of the bleached enamel, but with no major changes to the composition of the enamel.…”
Section: Souza and Othersmentioning
confidence: 99%
“…Therefore, the bleaching mechanisms do not differ greatly between the two agents. Furthermore, free radicals theoretically act on organic substances and have been thought to have no effect on inorganic substances [5][6] .…”
Section: ) Hr-tem Observationmentioning
confidence: 99%
“…Hydroxyl radicals generated by decomposition of the main ingredient hydrogen peroxide or carbamide peroxide are unstable compounds possessing very strong polarity, and they cleave the color-imparting molecular chains of organic substances, converting them into small molecular substances with nearly no color. Therefore, bleaching is a process of decoloration by decomposing organic substances, and has been regarded to have no effect on inorganic substances 5,6) . On the other hand, changes in micro structure of the enamel surface have been observed under a scanning electron microscope, and spot-like depressed structures have been reported.…”
Section: Introductionmentioning
confidence: 99%